Effects of different packages on broccoli integrity and quality: A scientific approach - Guimarães, Valdeir de Oliveira; e Silva, Vitória Jakeline Ornelas; Alves, Gabriela Andrade; de Oliveira, Ana Paula C.; Mendes, Fabrícia Queiroz (Seven Editora, 2024)
Broccoli, as it is a vegetable rich in moisture, is extremely perishable and its commercialization faces problems due to this short shelf life. Packaging and coatings become great allies in the conservation of this product for a longer period. Thus, the present study aimed to evaluate the influence of the use of different types of packaging and edible coating on the conservation and quality of broccoli. The vegetables were arranged in plastic film and parchment paper packages and, for another treatment, a starch-based coating was produced. The treatments were evaluated on day 0 and also on day 7 in terms of mass loss and also in relation to color. The data were analyzed using Tukey's mean test of 5% probability. The results showed the lowest percentage of mass loss for broccoli packed with plastic wrap and the highest average was found for vegetables that were coated with starch solution. Regarding the color parameters, no significant differences were detected for the treatments. However, visually, the broccoli submitted to starch coating showed less color variation. Finally, it was concluded that more satisfactory results were found for vegetables packed with plastic film, as they presented less mass loss. On the other hand, visually, starch-coated broccoli has greater conservation in the color of the product. Therefore, it is suggested to combine both treatments to obtain more advantageous results. DOI:https://doi.org/10.56238/sevened2024.018-023